Mobilnostni načrt za Splošno bolnišnico Novo mesto - Urh, Vane (Revija za geografijo, 2024)
The article presents the process of creating a mobility plan for the General Hospital Novo mesto and its contribution to reducing the environmental impact of healthcare and traffic sectors. An analysis of travel habits and measures that contributed to the promotion and awareness of sustainable mobility in a location that generates a lot of traffic are specifically presented. Additionally, by an importance-performance analysis, we tried to determine the factors that could most influence the change in travel habits in the direction of more sustainable mobility. Change of modal split in favour of more sustainable mobility will contribute to the green transition and have an impact to adaptation and mitigation of climate change.
Keywords: climate changes; mobility planning; mobilnostni načrti; podnebna odpornost; podnebne spremembe; potovalne navade; travel habits